'On viewing: the politics of looking at the corpse': a reply. Issue 2 (3rd July 2017) - Heath-Kelly, Charlotte
Abstract : This is a reply to: Auchter, Jessica. 2017. "On viewing: the politics of looking at the corpse." Global Discourse . 7 (2–3): 223–238.https://doi.org/10.1080/23269995.2017.1314908 .